2011
DOI: 10.1111/j.1477-2574.2011.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin levels predict malignancy in patients with obstructive jaundice

Abstract: In patients with obstructive jaundice, bilirubin levels in isolation represent an important tool for discriminating between benign and malignant underlying causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 17 publications
6
50
0
1
Order By: Relevance
“…In this study jaundice duration was significantly longer among suspected tumor patients (P value = 0.01), which is comparable to a study done by Giuseppe Garcea et al [18] ;…”
Section: Discussionsupporting
confidence: 91%
“…In this study jaundice duration was significantly longer among suspected tumor patients (P value = 0.01), which is comparable to a study done by Giuseppe Garcea et al [18] ;…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with one large retrospective analysis by Garcea and colleagues who included 1026 patients. They found bilirubin levels >5.8 mg/dL highly predictive of malignancy . Two previous published studies with only small patient numbers also showed a positive correlation with malignant bile duct obstruction in bilirubin levels greater than 4.4 and 5 mg/dL respectively .…”
Section: Discussionmentioning
confidence: 80%
“…Although choledocholithiasis might be suggested as the pathogenesis, it is rare for a single factor to cause such severe jaundice. As jaundice is commonly associated with PVT, the critical jaundice in our patient was likely induced by obstruction due to common bile duct calculus and PVT, rather than a single obstructive factor, which is typically associated with much lower bilirubin levels than seen in our patient . Because C. sinensis flukes were not observed in the bile ducts, the flukes themselves did not appear to be the cause of the mechanical obstruction.…”
Section: Discussionmentioning
confidence: 75%